A kind of highly corrosion-resistant marine engineering concrete and preparation method thereof
Through basalt fiber modification technology and gradient concentration alkaline silica sol treatment, combined with fly ash and calcium sulfaluminate, the problem of poor durability of marine concrete is solved, and efficient erosion resistance and strength improvement is achieved, which is suitable for use in marine environments.
Patent Information
- Application Number
- CN202310350454.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-04
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-04-04
AI Technical Summary
Existing marine concrete has poor durability in marine environments and is susceptible to factors such as wet and dry corrosion, sulfate corrosion, and existing anti-corrosion measures can only slow down corrosion from the surface, making it difficult to significantly improve corrosion resistance while ensuring strength.
Using basalt fiber modification technology, the modified fibers are treated with pretreatment and gradient concentration alkaline silica sol to enhance the hydrophilic properties of the fiber surface and the adhesion of the silica sol, forming an irregular network distribution, improving the density and permeability of concrete and add fly ash and calcium sulfaluminate to enhance structural stability and crack resistance.
It significantly improves the corrosion resistance and strength properties of marine concrete, and is suitable for use in complex marine environments. The compressive strength of 28d is not less than 60MPa and the chloride ion diffusion coefficient is less than 2, meeting the needs of marine engineering.
Smart Images

Figure CN116375425B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of marine engineering concrete, and particularly relates to a highly corrosion-resistant marine engineering concrete and a preparation method thereof. Background Art
[0002] Marine resources have laid a material foundation for human survival and development, and also affect the changes in the earth's environment. my country attaches great importance to the development of the marine economy and gives the ocean a very high strategic position in international competition. The construction and development of marine engineering in my country has also received close attention.
[0003] Concrete plays an irreplaceable role in engineering construction due to its superior performance and low cost, and also becomes the most used material in marine engineering. In order to adapt to the erosion of seawater and the harsh natural climate of the ocean, the concrete buildings in marine engineering must be strong, safe, sustainable and economical. However, the durability of concrete in the marine environment will be seriously damaged by various factors such as dry and wet erosion, sulfate erosion, etc.
[0004] In marine engineering construction, the durability and corrosion resistance of concrete used in marine construction projects are particularly important because seawater is rich in chloride ions and sulfates, which are extremely corrosive to concrete. One of the main reasons is the concrete itself. The alkaline substances in the concrete react with the acidic substances, causing the pH value of the concrete pore solution to decrease, thereby reducing the alkalinity of the concrete and causing the steel bars to lose the protection of the passivation layer.
[0005] The second is the chloride ions carried by the concrete itself and rich in seawater. The chloride ions have a small radius and strong penetrating ability. They are extremely strong depassivating agents. The chloride ions are adsorbed on the local passivation film, causing the pH value there to drop rapidly, thereby destroying the passivation film on the surface of the steel bar and accelerating the corrosion of the steel bar.
[0006] Third, due to the infiltration of seawater, the magnesium salts and sulfates in the seawater react with the calcium hydroxide in the cement stone to form magnesium hydroxide, ettringite, magnesium silicate hydrate, calcium chloride and gypsum. Magnesium hydroxide destroys the structure of the cement paste; once ettringite is formed, it can cause great internal stress in the concrete, causing the concrete to expand and crack; the substitution reaction of magnesium silicate hydrate on calcium silicate hydrate reduces the strength of the concrete and makes it brittle; calcium chloride and gypsum are soluble in water, resulting in increased leaching of the concrete, followed by loss of strength and quality.
[0007] In addition, factors such as freezing, high temperature and microbial corrosion can corrode concrete, resulting in poor durability.
[0008] At present, in order to prevent seawater from corroding concrete and then steel bars, one method is to apply anti-corrosion paint on the surface of concrete to prevent corrosion; to apply an anti-corrosion layer on the surface of steel bars to slow down the corrosion of steel bars; and to use electrochemical methods for anti-corrosion. However, these anti-corrosion methods can only slow down the corrosion of concrete and steel bars from the surface. Once the anti-corrosion layer is damaged, the erosion rate will be accelerated.
[0009] There are also some improvements in the matching of concrete raw materials. For example, patent application CN111302729A discloses a lightweight high-strength concrete, which contains 550-650 parts of cement, 250-350 parts of nano-active materials, 250-350 parts of iron ore powder, 100-150 parts of glass beads, 100-120 parts of shale sand, 350-450 parts of spherical coarse aggregate, 135-150 parts of water, 20-30 parts of admixtures, and 50-100 parts of steel fibers. However, the coarse aggregate and sand used in the invention have large particle sizes, the aggregate and cementitious material particles are not tightly stacked, and the interface transition zone is weak; and the coarse aggregate needs to be pre-wetted for 24 hours in advance and dried naturally to control its moisture content, which is complicated and difficult to construct, and the overall strength and corrosion resistance of the material are not high. Therefore, how to ensure the strength performance of marine engineering concrete while greatly improving its corrosion resistance is a technical problem that needs to be solved urgently. Summary of the invention
[0010] In view of the problems existing in the prior art, the present invention provides a highly corrosion-resistant concrete modified by basalt fiber, which improves the corrosion resistance of marine engineering concrete while improving its strength and durability, thus meeting the use requirements of concrete in the marine environment.
[0011] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:
[0012] A highly erosion-resistant marine engineering concrete is prepared from the following raw materials in parts by weight: 300-400 parts of cement, 500-600 parts of fine aggregate, 400-500 parts of coarse aggregate, 50-100 parts of fly ash, 100-150 parts of water, 10-20 parts of filler, 20-30 parts of mixed modified fiber, 1-3 parts of water reducing agent, 1-3 parts of urea, and 1-3 parts of calcium sulfoaluminate.
[0013] Furthermore, the cement is P·O42.5 ordinary Portland cement.
[0014] Furthermore, the fine aggregate is river sand with a fineness modulus of 2.89, and the coarse aggregate is ordinary limestone crushed stone with a continuous grading of 5-10 mm.
[0015] Furthermore, the filler is quartz powder and / or corundum powder.
[0016] Furthermore, the specific preparation method of the mixed modified fiber is:
[0017] (1) Pretreatment: The basalt fiber is dispersed in an acid solution at a solid-liquid ratio of 1 g: 100 mL, and then 0.1% benzyl alcohol by weight of the mixed solution is added. After ultrasonic dispersion for 1-2 hours, the basalt fiber is filtered, and the basalt fiber is repeatedly washed with deionized water and dried to obtain the pretreated basalt fiber;
[0018] (2) ultrasonically dispersing the pretreated basalt fiber in an alkaline silica sol solution with a silica content of 9-10% for 1-2 h; filtering and removing, and dispersing again in an alkaline silica sol solution with a silica content of 19-20% for 1-2 h; filtering and removing, and finally dispersing in an alkaline silica sol solution with a silica content of 29-30% for 1-2 h. After the treatment is completed, the pretreated basalt fiber is fully dried to obtain a mixed modified fiber.
[0019] Furthermore, the acid solution in step (1) is nitric acid with a mass concentration of 10-20%.
[0020] Furthermore, the pH of the alkaline silica sol solution in step (2) is 9-10, and the particle size of the silica is 10-20 nm.
[0021] Furthermore, the water reducing agent is a polycarboxylic acid type high performance water reducing agent, and its water reducing rate is greater than 25%.
[0022] A method for preparing highly corrosion-resistant marine engineering concrete comprises the following preparation steps:
[0023] (1) preparing mixed modified fibers;
[0024] (2) mixing cement, fine aggregate, coarse aggregate, fly ash, filler, urea and calcium sulphoaluminate by weight under mechanical stirring to obtain a dry material;
[0025] (3) Add water and water reducing agent to the dry material and mix them evenly, then add the prepared mixed modified fiber along the stirring direction, mix them evenly, and obtain highly erosion-resistant marine concrete.
[0026] All raw materials of the present invention are commercially available.
[0027] In the preparation of marine engineering concrete, in order to improve the corrosion resistance and strength of concrete, the existing technology usually uses fibers or nanoparticles (such as nano-grade silica sol) to improve the density of the system. However, in practical applications, fibers are very likely to be unevenly distributed, resulting in agglomeration and other phenomena, leading to stress concentration and reduced mechanical properties. At the same time, the bonding force between fibers and nanoparticles is poor, and the filling effect of nanoparticles cannot be effectively exerted. Therefore, in most cases, the simple addition and soaking of fibers and nanoparticles such as silica sol cannot achieve the expected technical effect.
[0028] Therefore, the present invention first pre-treats the basalt fiber to improve the roughness of the fiber surface, and modifies the benzyl alcohol to increase the hydrophilicity of the surface, which is more conducive to the subsequent attachment of silica sol particles. Secondly, the fiber is modified using a gradually increasing gradient concentration of alkaline silica sol. The gradient concentration treatment from low to high can, on the one hand, make the nano-scale silica sol particles evenly and densely attached to the fiber, reduce the agglomeration effect of the fiber itself, and at the same time, it can also promote the uniform distribution of silica sol and enhance its filling effect. The interaction between the two makes the fiber in the concrete present an irregular network distribution. This distribution condition divides the concrete into countless small pieces, reduces the diffusion coefficient of corrosion particles such as chloride ions, limits the development of pores and cracks inside the concrete, and improves the concrete's impermeability and erosion resistance. At the same time, the fiber and silica sol also play a bridging role, a toughening role, and a filling role, effectively reducing the carbonization rate of the concrete, improving the system density, and improving the strength performance of the concrete.
[0029] The present invention also adds a certain proportion of fly ash, and the fly ash reacts chemically with calcium hydroxide or other alkaline earth metal hydroxides to generate a compound with hydraulic cementing properties, so that the marine engineering concrete maintains good and stable structural strength; the added urea can make the marine engineering concrete have good impermeability while maintaining good structural strength, so that during the use of the marine engineering concrete, the various component raw materials can maintain good and stable interface bonding strength, and the stability of the marine engineering concrete is enhanced; calcium sulfoaluminate can offset or partially offset the tensile stress generated by shrinkage deformation when the pre-compression stress is poured into the concrete, improve the crack resistance of the marine engineering concrete, avoid the generation of early cracks, and thus ensure the overall impermeability of the marine engineering concrete.
[0030] Beneficial Effects
[0031] The present invention uses gradient low-concentration silica sol to prepare modified fibers, which are added to marine engineering concrete after compounding, greatly improving the corrosion resistance and strength performance of the concrete. The preparation process is simple, and the obtained concrete has good comprehensive performance and is suitable for use in complex marine environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The internal morphology electron microscope pictures of the concrete obtained in Example 4 and Comparative Examples 1-3 of the present invention after 28 days of test curing, wherein A is Example 4, B is Comparative Example 1, C is Comparative Example 2, and D is Comparative Example 3. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.
[0034] Example 1
[0035] A highly erosion-resistant marine engineering concrete is prepared from the following raw materials in parts by weight: 300 parts of cement, 500 parts of fine aggregate, 400 parts of coarse aggregate, 50 parts of fly ash, 100 parts of water, 10 parts of filler, 20 parts of mixed modified fiber, 1 part of water reducing agent, 1 part of urea, and 1 part of calcium sulfoaluminate.
[0036] The cement is P·O42.5 ordinary Portland cement.
[0037] The fine aggregate is river sand with a fineness modulus of 2.89, and the coarse aggregate is ordinary limestone crushed stone with a continuous grading of 5-10 mm.
[0038] The filler is quartz powder.
[0039] The specific preparation method of the mixed modified fiber is:
[0040] (1) Pretreatment: The basalt fiber was dispersed in an acid solution at a solid-liquid ratio of 1 g: 100 mL, and then 0.1% benzyl alcohol by weight of the mixed solution was added. After ultrasonic dispersion for 1 h, the basalt fiber was filtered, and the basalt fiber was repeatedly washed with deionized water and dried to obtain the pretreated basalt fiber;
[0041] (2) ultrasonically dispersing the pretreated basalt fiber in an alkaline silica sol solution with a silica content of 9-10%, and ultrasonically treating it for 1 hour; filtering and removing, and dispersing again in an alkaline silica sol solution with a silica content of 19-20% and ultrasonically treating it for 1 hour; filtering and removing, and finally dispersing in an alkaline silica sol solution with a silica content of 29-30% and ultrasonically treating it for 1 hour. After the treatment is completed, it is fully dried to obtain a mixed modified fiber.
[0042] The acid solution in step (1) is nitric acid with a mass concentration of 10%.
[0043] The pH of the alkaline silica sol solution in step (2) is 9-10, and the particle size of the silicon dioxide is 10-20 nm.
[0044] The water reducing agent is a polycarboxylic acid type high performance water reducing agent, and its water reducing rate is greater than 25%.
[0045] A method for preparing highly corrosion-resistant marine engineering concrete comprises the following preparation steps:
[0046] (1) preparing mixed modified fibers;
[0047] (2) mixing cement, fine aggregate, coarse aggregate, fly ash, filler, urea and calcium sulphoaluminate by weight under mechanical stirring to obtain a dry material;
[0048] (3) Add water and water reducing agent to the dry material and mix them evenly, then add the prepared mixed modified fiber along the stirring direction, mix them evenly, and obtain highly erosion-resistant marine concrete.
[0049] Example 2
[0050] A highly erosion-resistant marine engineering concrete is prepared from the following raw materials in parts by weight: 380 parts of cement, 550 parts of fine aggregate, 430 parts of coarse aggregate, 60 parts of fly ash, 120 parts of water, 15 parts of filler, 24 parts of mixed modified fiber, 2 parts of water reducing agent, 2 parts of urea, and 2 parts of calcium sulfoaluminate.
[0051] The cement is P·O42.5 ordinary Portland cement.
[0052] The fine aggregate is river sand with a fineness modulus of 2.89, and the coarse aggregate is ordinary limestone crushed stone with a continuous grading of 5-10 mm.
[0053] The filler is corundum powder.
[0054] The specific preparation method of the mixed modified fiber is:
[0055] (1) Pretreatment: The basalt fiber was dispersed in an acid solution at a solid-liquid ratio of 1 g: 100 mL, and then 0.1% benzyl alcohol by weight of the mixed solution was added. After ultrasonic dispersion for 1.5 h, the mixture was filtered, and the basalt fiber was repeatedly washed with deionized water and dried to obtain the pretreated basalt fiber.
[0056] (2) ultrasonically dispersing the pretreated basalt fiber in an alkaline silica sol solution with a silica content of 9-10% for 1.5 h; filtering and removing, and dispersing again in an alkaline silica sol solution with a silica content of 19-20% for 1.5 h; filtering and removing, and finally dispersing in an alkaline silica sol solution with a silica content of 29-30% for 1.5 h. After the treatment is completed, the fiber is fully dried to obtain a mixed modified fiber.
[0057] The acid solution in step (1) is nitric acid with a mass concentration of 15%.
[0058] The pH of the alkaline silica sol solution in step (2) is 9-10, and the particle size of the silicon dioxide is 10-20 nm.
[0059] The water reducing agent is a polycarboxylic acid type high performance water reducing agent, and its water reducing rate is greater than 25%.
[0060] A method for preparing highly corrosion-resistant marine engineering concrete comprises the following preparation steps:
[0061] (1) preparing mixed modified fibers;
[0062] (2) mixing cement, fine aggregate, coarse aggregate, fly ash, filler, urea and calcium sulphoaluminate by weight under mechanical stirring to obtain a dry material;
[0063] (3) Add water and water reducing agent to the dry material and mix them evenly, then add the prepared mixed modified fiber along the stirring direction, mix them evenly, and obtain highly erosion-resistant marine concrete.
[0064] Example 3
[0065] A highly erosion-resistant marine engineering concrete is prepared from the following raw materials in parts by weight: 360 parts of cement, 550 parts of fine aggregate, 450 parts of coarse aggregate, 70 parts of fly ash, 130 parts of water, 15 parts of filler, 26 parts of mixed modified fiber, 2 parts of water reducing agent, 2 parts of urea, and 2 parts of calcium sulfoaluminate.
[0066] The cement is P·O42.5 ordinary Portland cement.
[0067] The fine aggregate is river sand with a fineness modulus of 2.89, and the coarse aggregate is ordinary limestone crushed stone with a continuous grading of 5-10 mm.
[0068] The filler is quartz powder.
[0069] The specific preparation method of the mixed modified fiber is:
[0070] (1) Pretreatment: The basalt fiber was dispersed in an acid solution at a solid-liquid ratio of 1 g: 100 mL, and then 0.1% benzyl alcohol by weight of the mixed solution was added. After ultrasonic dispersion for 2 h, the basalt fiber was filtered, and the basalt fiber was repeatedly washed with deionized water and dried to obtain the pretreated basalt fiber;
[0071] (2) ultrasonically dispersing the pretreated basalt fiber in an alkaline silica sol solution with a silica content of 9-10% and ultrasonically treating it for 2 hours; filtering and removing, and dispersing again in an alkaline silica sol solution with a silica content of 19-20% and ultrasonically treating it for 2 hours; filtering and removing, and finally dispersing in an alkaline silica sol solution with a silica content of 29-30% and ultrasonically treating it for 2 hours. After the treatment is completed, it is fully dried to obtain a mixed modified fiber.
[0072] The acid solution in step (1) is nitric acid with a mass concentration of 20%.
[0073] The pH of the alkaline silica sol solution in step (2) is 9-10, and the particle size of the silicon dioxide is 10-20 nm.
[0074] The water reducing agent is a polycarboxylic acid type high performance water reducing agent, and its water reducing rate is greater than 25%.
[0075] A method for preparing highly corrosion-resistant marine engineering concrete comprises the following preparation steps:
[0076] (1) preparing mixed modified fibers;
[0077] (2) mixing cement, fine aggregate, coarse aggregate, fly ash, filler, urea and calcium sulphoaluminate by weight under mechanical stirring to obtain a dry material;
[0078] (3) Add water and water reducing agent to the dry material and mix them evenly, then add the prepared mixed modified fiber along the stirring direction, mix them evenly, and obtain highly erosion-resistant marine concrete.
[0079] Example 4
[0080] A highly erosion-resistant marine engineering concrete is prepared from the following raw materials in parts by weight: 400 parts of cement, 600 parts of fine aggregate, 500 parts of coarse aggregate, 100 parts of fly ash, 150 parts of water, 20 parts of filler, 30 parts of mixed modified fiber, 3 parts of water reducing agent, 3 parts of urea, and 3 parts of calcium sulfoaluminate.
[0081] The cement is P·O42.5 ordinary Portland cement.
[0082] The fine aggregate is river sand with a fineness modulus of 2.89, and the coarse aggregate is ordinary limestone crushed stone with a continuous grading of 5-10 mm.
[0083] The filler is corundum powder.
[0084] The specific preparation method of the mixed modified fiber is:
[0085] (1) Pretreatment: The basalt fiber was dispersed in an acid solution at a solid-liquid ratio of 1 g: 100 mL, and then 0.1% benzyl alcohol by weight of the mixed solution was added. After ultrasonic dispersion for 2 h, the basalt fiber was filtered, and the basalt fiber was repeatedly washed with deionized water and dried to obtain the pretreated basalt fiber;
[0086] (2) ultrasonically dispersing the pretreated basalt fiber in an alkaline silica sol solution with a silica content of 9-10% and ultrasonically treating it for 2 hours; filtering and removing, and dispersing again in an alkaline silica sol solution with a silica content of 19-20% and ultrasonically treating it for 2 hours; filtering and removing, and finally dispersing in an alkaline silica sol solution with a silica content of 29-30% and ultrasonically treating it for 2 hours. After the treatment is completed, it is fully dried to obtain a mixed modified fiber.
[0087] The acid solution in step (1) is nitric acid with a mass concentration of 20%.
[0088] The pH of the alkaline silica sol solution in step (2) is 9-10, and the particle size of the silicon dioxide is 10-20 nm.
[0089] The water reducing agent is a polycarboxylic acid type high performance water reducing agent, and its water reducing rate is greater than 25%.
[0090] A method for preparing highly corrosion-resistant marine engineering concrete comprises the following preparation steps:
[0091] (1) preparing mixed modified fibers;
[0092] (2) mixing cement, fine aggregate, coarse aggregate, fly ash, filler, urea and calcium sulphoaluminate by weight under mechanical stirring to obtain a dry material;
[0093] (3) Add water and water reducing agent to the dry material and mix them evenly, then add the prepared mixed modified fiber along the stirring direction, mix them evenly, and obtain highly erosion-resistant marine concrete.
[0094] Comparative Example 1
[0095] A highly erosion-resistant marine engineering concrete is prepared from the following raw materials in parts by weight: 400 parts of cement, 600 parts of fine aggregate, 500 parts of coarse aggregate, 100 parts of fly ash, 150 parts of water, 20 parts of filler, 30 parts of mixed modified fiber, 3 parts of water reducing agent, 3 parts of urea, and 3 parts of calcium sulfoaluminate.
[0096] The cement is P·O42.5 ordinary Portland cement.
[0097] The fine aggregate is river sand with a fineness modulus of 2.89, and the coarse aggregate is ordinary limestone crushed stone with a continuous grading of 5-10 mm.
[0098] The filler is corundum powder.
[0099] The specific preparation method of the mixed modified fiber is:
[0100] (1) Pretreatment: The basalt fiber was dispersed in an acid solution at a solid-liquid ratio of 1 g: 100 mL, and then 0.1% benzyl alcohol by weight of the mixed solution was added. After ultrasonic dispersion for 2 h, the basalt fiber was filtered, and the basalt fiber was repeatedly washed with deionized water and dried to obtain the pretreated basalt fiber;
[0101] (2) The pretreated basalt fiber is ultrasonically dispersed in an alkaline silica sol solution having a silicon dioxide content of 9-10%, and the solution is ultrasonically treated for 6 hours. After the treatment, the solution is fully dried to obtain a mixed modified fiber.
[0102] The acid solution in step (1) is nitric acid with a mass concentration of 20%.
[0103] The pH of the alkaline silica sol solution in step (2) is 9-10, and the particle size of the silicon dioxide is 10-20 nm.
[0104] The water reducing agent is a polycarboxylic acid type high performance water reducing agent, and its water reducing rate is greater than 25%.
[0105] A method for preparing highly corrosion-resistant marine engineering concrete comprises the following preparation steps:
[0106] (1) preparing mixed modified fibers;
[0107] (2) mixing cement, fine aggregate, coarse aggregate, fly ash, filler, urea and calcium sulphoaluminate by weight under mechanical stirring to obtain a dry material;
[0108] (3) Add water and water reducing agent to the dry material and mix them evenly, then add the prepared mixed modified fiber along the stirring direction, mix them evenly, and obtain highly erosion-resistant marine concrete.
[0109] (4) In this comparative example, except that only an alkaline silica sol solution with a silica content of 9-10% was used for treatment when mixing the modified fibers, the remaining raw materials and preparation methods were the same as those of Example 4.
[0110] Comparative Example 2
[0111] A highly erosion-resistant marine engineering concrete is prepared from the following raw materials in parts by weight: 400 parts of cement, 600 parts of fine aggregate, 500 parts of coarse aggregate, 100 parts of fly ash, 150 parts of water, 20 parts of filler, 30 parts of mixed modified fiber, 3 parts of water reducing agent, 3 parts of urea, and 3 parts of calcium sulfoaluminate.
[0112] The cement is P·O42.5 ordinary Portland cement.
[0113] The fine aggregate is river sand with a fineness modulus of 2.89, and the coarse aggregate is ordinary limestone crushed stone with a continuous grading of 5-10 mm.
[0114] The filler is corundum powder.
[0115] The specific preparation method of the mixed modified fiber is:
[0116] (1) Pretreatment: The basalt fiber was dispersed in an acid solution at a solid-liquid ratio of 1 g: 100 mL, and then 0.1% benzyl alcohol by weight of the mixed solution was added. After ultrasonic dispersion for 2 h, the basalt fiber was filtered, and the basalt fiber was repeatedly washed with deionized water and dried to obtain the pretreated basalt fiber;
[0117] (2) ultrasonically dispersing the pretreated basalt fiber in an alkaline silica sol solution having a silica content of 19-20%,
[0118] The fiber was ultrasonically treated for 6 h and then fully dried to obtain mixed modified fibers.
[0119] The acid solution in step (1) is nitric acid with a mass concentration of 20%.
[0120] The pH of the alkaline silica sol solution in step (2) is 9-10, and the particle size of the silicon dioxide is 10-20 nm.
[0121] The water reducing agent is a polycarboxylic acid type high performance water reducing agent, and its water reducing rate is greater than 25%.
[0122] A method for preparing highly corrosion-resistant marine engineering concrete comprises the following preparation steps:
[0123] (1) preparing mixed modified fibers;
[0124] (2) mixing cement, fine aggregate, coarse aggregate, fly ash, filler, urea and calcium sulphoaluminate by weight under mechanical stirring to obtain a dry material;
[0125] (3) Add water and water reducing agent to the dry material and mix them evenly, then add the prepared mixed modified fiber along the stirring direction, mix them evenly, and obtain highly erosion-resistant marine concrete.
[0126] In this comparative example, except that only an alkaline silica sol solution with a silicon dioxide content of 19-20% was used for treatment when mixing the modified fibers, the remaining raw materials and preparation methods were the same as those of Example 4.
[0127] Comparative Example 3
[0128] A highly erosion-resistant marine engineering concrete is prepared from the following raw materials in parts by weight: 400 parts of cement, 600 parts of fine aggregate, 500 parts of coarse aggregate, 100 parts of fly ash, 150 parts of water, 20 parts of filler, 30 parts of mixed modified fiber, 3 parts of water reducing agent, 3 parts of urea, and 3 parts of calcium sulfoaluminate.
[0129] The cement is P·O42.5 ordinary Portland cement.
[0130] The fine aggregate is river sand with a fineness modulus of 2.89, and the coarse aggregate is ordinary limestone crushed stone with a continuous grading of 5-10 mm.
[0131] The filler is corundum powder.
[0132] The specific preparation method of the mixed modified fiber is:
[0133] (1) Pretreatment: The basalt fiber was dispersed in an acid solution at a solid-liquid ratio of 1 g: 100 mL, and then 0.1% benzyl alcohol by weight of the mixed solution was added. After ultrasonic dispersion for 2 h, the basalt fiber was filtered, and the basalt fiber was repeatedly washed with deionized water and dried to obtain the pretreated basalt fiber;
[0134] (2) ultrasonically dispersing the pretreated basalt fiber in an alkaline silica sol solution having a silica content of 29-30%,
[0135] The fiber was ultrasonically treated for 6 h and then fully dried to obtain mixed modified fibers.
[0136] The acid solution in step (1) is nitric acid with a mass concentration of 20%.
[0137] The pH of the alkaline silica sol solution in step (2) is 9-10, and the particle size of the silicon dioxide is 10-20 nm.
[0138] The water reducing agent is a polycarboxylic acid type high performance water reducing agent, and its water reducing rate is greater than 25%.
[0139] A method for preparing highly corrosion-resistant marine engineering concrete comprises the following preparation steps:
[0140] (1) preparing mixed modified fibers;
[0141] (2) mixing cement, fine aggregate, coarse aggregate, fly ash, filler, urea and calcium sulphoaluminate by weight under mechanical stirring to obtain a dry material;
[0142] (3) Add water and water reducing agent to the dry material and mix them evenly, then add the prepared mixed modified fiber along the stirring direction, mix them evenly, and obtain highly erosion-resistant marine concrete.
[0143] In this comparative example, except that only an alkaline silica sol solution with a silicon dioxide content of 29-30% was used for treatment when mixing the modified fibers, the remaining raw materials and preparation methods were the same as those of Example 4.
[0144] Comparative Example 4
[0145] A highly erosion-resistant marine concrete is prepared from the following raw materials in parts by weight: 400 parts of cement, 600 parts of fine aggregate, 500 parts of coarse aggregate, 100 parts of fly ash, 150 parts of water, 20 parts of filler, 30 parts of modified fiber, 3 parts of water reducing agent, 3 parts of urea, and 3 parts of calcium sulfoaluminate.
[0146] The cement is P·O42.5 ordinary Portland cement.
[0147] The fine aggregate is river sand with a fineness modulus of 2.89, and the coarse aggregate is ordinary limestone crushed stone with a continuous grading of 5-10 mm.
[0148] The filler is corundum powder.
[0149] The specific preparation method of the modified fiber is as follows: basalt fiber is dispersed in an acid solution at a solid-liquid ratio of 1g:100mL, benzyl alcohol is added at 0.1% by mass of the mixed solution, ultrasonically dispersed for 2h, filtered, the basalt fiber is repeatedly washed with deionized water, and dried to obtain the modified fiber;
[0150] The acid solution is nitric acid with a mass concentration of 20%.
[0151] The pH of the alkaline silica sol solution in step (2) is 9-10, and the particle size of the silicon dioxide is 10-20 nm.
[0152] The water reducing agent is a polycarboxylic acid type high performance water reducing agent, and its water reducing rate is greater than 25%.
[0153] A method for preparing highly corrosion-resistant marine engineering concrete comprises the following preparation steps:
[0154] (1) preparing modified fibers;
[0155] (2) mixing cement, fine aggregate, coarse aggregate, fly ash, filler, urea and calcium sulphoaluminate by weight under mechanical stirring to obtain a dry material;
[0156] (3) Add water and water reducing agent to the dry material and mix well, then add the prepared modified fiber along the stirring direction.
[0157] Mix thoroughly and evenly to obtain highly corrosion-resistant marine concrete.
[0158] In this comparative example, except that when modifying the fiber, only the first step of pretreatment modification is performed without gradient concentration silica sol modification, that is, only acid and benzyl alcohol are treated, the other raw materials and preparation methods are the same as those in Example 4.
[0159] Performance Testing
[0160] According to the mix ratios of Examples 1-4 and Comparative Examples 1-4, concrete was prepared by weighing raw materials for performance testing. According to the Standard for Performance Test Methods of Ordinary Concrete Mixtures (GB / T50080-2016), the concrete was placed in a standard curing room for 24 hours, then demolded, and the sample was placed in a standard curing box for curing to the specified age.
[0161] Detection Methods
[0162] (1) Concrete working performance test
[0163] The performance of concrete mixture is tested in accordance with the "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" (GB / T 50080-2016). The main indicators include initial slump / expansion, air content, and time loss of slump / expansion.
[0164] (2) Strength performance
[0165] Concrete specimens should comply with the provisions of the "Standard Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019), prepare cubic specimens with dimensions of 100mm×100mm×100mm, cure them to the specified age under standard curing conditions, and conduct compressive strength tests on concrete specimens using a testing machine in the laboratory.
[0166] (3) Chloride ion permeability, electrical flux, and sulfate corrosion resistance
[0167] The chloride ion diffusion coefficient was tested according to the rapid chloride ion migration coefficient method, i.e., RCM method, in the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete (GB / T 50082-2009); at the same time, the electric flux and dry-wet cycle sulfate corrosion performance were tested according to this standard.
[0168] (4) Microstructure
[0169] SEM field emission scanning electron microscope
[0170] Table 1 Performance test results
[0171]
[0172] From the data in the table, we can see that the concrete of the embodiment of the present invention exhibits good working performance, with a 28d compressive strength of not less than 60MPa and a chloride ion diffusion coefficient of less than 2, which fully meets the use requirements of the special marine environment. In contrast, in Comparative Examples 1-4, the modification process of the fiber with a gradient concentration of silica sol was changed. Since the silica sol particles could not be evenly and densely attached to the fiber, the modification effect of the silica sol decreased, resulting in a decrease in the comprehensive performance of the concrete. It can also be seen from the SEM image of the microscopic morphology of the concrete after 28 days of curing that the concrete obtained in Example 4 of the present invention has densely filled fibers and hydration products, and has the best density, while Comparative Examples 1-3 all present local holes and reduced density.
[0173] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
Claims
1. A highly corrosion-resistant marine concrete, characterized in that: The mixed modified fiber is prepared from the following raw materials in parts by weight: 300-400 parts of cement, 500-600 parts of fine aggregate, 400-500 parts of coarse aggregate, 50-100 parts of fly ash, 100-150 parts of water, 10-20 parts of filler, 20-30 parts of mixed modified fiber, 1-3 parts of water reducing agent, 1-3 parts of urea, and 1-3 parts of calcium sulfoaluminate; the specific preparation method of the mixed modified fiber is: (1) Pretreatment: The basalt fiber was dispersed in an acid solution at a solid-liquid ratio of 1 g: 100 mL, and then 0.1% benzyl alcohol by weight of the mixed solution was added. After ultrasonic dispersion for 1-2 h, the basalt fiber was filtered, and the basalt fiber was repeatedly washed with deionized water and dried to obtain the pretreated basalt fiber. (2) ultrasonically dispersing the pretreated basalt fiber in an alkaline silica sol solution with a silica content of 9-10% for 1-2 h; filtering and removing, and dispersing again in an alkaline silica sol solution with a silica content of 19-20% for 1-2 h; filtering and removing, and finally dispersing in an alkaline silica sol solution with a silica content of 29-30% for 1-2 h. After the treatment, the pretreated basalt fiber is fully dried to obtain a mixed modified fiber.
2. The highly corrosion-resistant marine concrete according to claim 1, characterized in that: The cement is P•O42.5 ordinary Portland cement.
3. The highly corrosion-resistant marine concrete according to claim 1, characterized in that: The fine aggregate is river sand with a fineness modulus of 2.89, and the coarse aggregate is ordinary limestone crushed stone with a continuous grading of 5-10 mm.
4. The highly corrosion-resistant marine concrete according to claim 1, characterized in that: The filler is quartz powder and / or corundum powder.
5. The highly corrosion-resistant marine concrete according to claim 1, characterized in that: In the preparation of the mixed modified fiber, the acid solution in step (1) is nitric acid with a mass concentration of 10-20%.
6. The highly corrosion-resistant marine concrete according to claim 1, characterized in that: In the preparation of the mixed modified fiber, the pH of the alkaline silica sol solution in step (2) is 9-10, and the particle size of the silica is 10-20 nm.
7. The highly corrosion-resistant marine concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid type high performance water reducing agent, and its water reducing rate is greater than 25%.
8. A method for preparing the highly corrosion-resistant marine concrete according to any one of claims 1 to 7, characterized in that: The method comprises the following preparation steps: (1) Preparation of mixed modified fibers; (2) mixing cement, fine aggregate, coarse aggregate, fly ash, filler, urea and calcium sulphoaluminate by weight under mechanical stirring to obtain a dry material; (3) Add water and water reducing agent to the dry material and mix them evenly, then add the prepared mixed modified fiber along the stirring direction and mix them evenly to obtain highly corrosion-resistant marine concrete.
Citation Information
Patent Citations
Lightweight high-strength concrete and preparation method thereof
CN111302729A
SiC fiber and fabric and preparation method thereof
CN101660225A
Anti-cracking / corrosion-resistant concrete and preparation method and application thereof, concrete pressure pipe and preparation method thereof
CN109320167A